2019
DOI: 10.5812/ijhrba.92807
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Susceptibility to Fluconazole and Voriconazole in Oral Candida glabrata Isolates from Drug Addicts

Abstract: Background: Candidiasis is a spectrum of opportunistic fungal diseases that can manifest in drug addicts in various forms, such as stomatitis. Objectives: This study aimed to determine the prevalence of oral candidiasis caused by Candida glabrata in addicts and examine the susceptibility of isolates to two azoles. Patients and Methods: After taking oral samples from 131 drug addicts suspected of having oral candidiasis, Candida species were identified by culture on chromogenic Candida agar, carbohydrate-assimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…To address this gap, we conducted this study in southwestern Iran and identified a noteworthy rate of OYC (67.3%) among drug abusers. Similarly, a study conducted in northeast Iran examined 83 oral samples from individuals with addiction and detected oral candidiasis in 61.8% of patients 19 . In another study conducted in central Iran, PCR results from oral samples showed a high frequency (69.8%) of Candida species among drug abusers 17 .…”
Section: Discussionmentioning
confidence: 97%
“…To address this gap, we conducted this study in southwestern Iran and identified a noteworthy rate of OYC (67.3%) among drug abusers. Similarly, a study conducted in northeast Iran examined 83 oral samples from individuals with addiction and detected oral candidiasis in 61.8% of patients 19 . In another study conducted in central Iran, PCR results from oral samples showed a high frequency (69.8%) of Candida species among drug abusers 17 .…”
Section: Discussionmentioning
confidence: 97%
“…The demographic data, including age, gender, and clinical history of cancer were documented for each patient. Candida isolates were identified by conventional morphological and biochemical methods (14,15). Finally, Candida species was confirmed by polymerase chain reaction (PCR) according to company protocol of Candida spp.…”
Section: Isolation Of Candida Speciesmentioning
confidence: 99%
“…Finally, Candida species was confirmed by polymerase chain reaction (PCR) according to company protocol of Candida spp. detection kit (Iranian Gene Fanavar Institute, Iran) using 18S rRNA universal primers (14).…”
Section: Isolation Of Candida Speciesmentioning
confidence: 99%
“…For example, according to certain studies, C. glabrata has intrinsic resistance to the azoles combinations, whereas Candida dubliniensis has relative resistance to such combinations. [ 30 31 ] The uncontrolled and unconventional use of antifungal drugs makes the species resistant and increases drug resistance, causing a lot of problems.…”
Section: Introductionmentioning
confidence: 99%